2021
DOI: 10.1007/s00415-021-10545-2
|View full text |Cite
|
Sign up to set email alerts
|

Disease-modifying therapies and SARS-CoV-2 vaccination in multiple sclerosis: an expert consensus

Abstract: Coronavirus disease (COVID-19) appeared in December 2019 in the Chinese city of Wuhan and has quickly become a global pandemic. The disease is caused by the severe acute respiratory syndrome coronavirus type-2 (SARS-CoV-2), an RNA beta coronavirus phylogenetically similar to SARS coronavirus. To date, more than 132 million cases of COVID19 have been recorded in the world, of which over 2.8 million were fatal (https://coronavirus.jhu.edu/map.html). A huge vaccination campaign has started around the world since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 78 publications
2
57
0
1
Order By: Relevance
“…Following the approval of COVID-19 vaccines across EU countries, vaccination programmes have been started in order to identify vulnerable people at highest risk from serious illness or death from COVID-19. According to recent recommendations from the Italian Ministry of Health and an Italian expert consensus, people with Multiple Sclerosis (MS), especially those with disabilities, progressive forms of the disease, older age, and comorbidities, were considered to be the category with the highest priority during the second phase of the Italian immunization programme (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Following the approval of COVID-19 vaccines across EU countries, vaccination programmes have been started in order to identify vulnerable people at highest risk from serious illness or death from COVID-19. According to recent recommendations from the Italian Ministry of Health and an Italian expert consensus, people with Multiple Sclerosis (MS), especially those with disabilities, progressive forms of the disease, older age, and comorbidities, were considered to be the category with the highest priority during the second phase of the Italian immunization programme (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…For non-live/inactivated vaccines, such as seasonal influenza vaccines, it is recommended to vaccinate patients treated with ocrelizumab since a protective humoral response can be expected, even if attenuated [ 60 ]. An expert consensus recently suggested that patients planned to receive ocrelizumab should be vaccinated at least 6 weeks before the first administration, whereas in those already receiving ocrelizumab, vaccinations should be administered at least 3 months after the last infusion [ 61 ].…”
Section: Safety and Tolerability Of Anti-cd20 Therapiesmentioning
confidence: 99%
“…• Cladribine is a purine analog which causes lymphocyte depletion by interfering with DNA synthesis, repair and cell metabolism. For cladribine, no conclusive data on vaccination are available yet, but multiple studies are currently being conducted (48,66). • Ocrelizumab, rituximab, and ofatumumab are anti-CD20 monoclonal antibodies leading to depletion of B cells in the circulation.…”
Section: Vaccination Is Protective Yet Partly Less Effective Under Certain Dmtmentioning
confidence: 99%
“…In this regard, monthly administered subcutaneous human B cell-depleting agent ofatumumab may offer the advantage of a shorter time span until CD19+ B cell repletion takes place (74). For ocrelizumab treatment, it is often suggested to vaccinate patients at the end of a treatment cycle with a minimum distance of four to six weeks to the next cycle (66,75). However, these experientially suggested time points need further confirmation in clinical studies.…”
Section: Vaccination Is Protective Yet Partly Less Effective Under Certain Dmtmentioning
confidence: 99%